Non-Neuronal Acetylcholine: The Missing Link Between Sepsis, Cancer, and Delirium? - Sfera, Adonis; Cummings, Michael; Osorio, Carolina (Frontiers in Medicine, 2015)
The interaction between living organisms and the environment requires a balancing act between genomic and epigenomic forces. Inflammation and cellular proliferation are kept in check by the genes, which code for their components and the microRNAs, which are capable of silencing the transcription of these genes. Acetylcholine (ACh) may play a unique role in the maintenance of this equilibrium, as the epigenomic inhibition of the gene coding for nicotinic receptors, and disinhibits the gene causing anergia in immune cells. We hypothesize that age-induced ACh deficiency is the result of an epigenomic dysfunction of microRNA-6775 (miR-6775), which silences the transcription of CHRNA7 gene [coding for alpha 7 nicotinic cholinergic receptors (nAChRs)]. When silenced, this gene induces decreased expression of alpha 7 nAChRs, which may predispose elderly individuals to inflammation, neuroinflammation, and delirium. We hypothesize further that miR-6775-induced hypocholinergia augments the expression of RNF 128, the gene related to anergy in lymphocytes (GRAIL). This gene favors regulatory T cells (Tregs), promoters of immunologic tolerance, which may predispose to both cancer and sepsis-induced immunosuppression.